2018
DOI: 10.9734/jeai/2018/43767
|View full text |Cite
|
Sign up to set email alerts
|

Application of Silicon to Alleviate Irrigation Water Salinity in Melon Growth

Abstract: Aims:The present study aimed to assess the alleviating effect of silicon in salinity on melon growth. Study Design: The experimental design was in randomised blocks, corresponding to the with four salt levels and three doses of silicon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…for the fresh and dry mass of the stem, reaching reductions of 59.8 and 97.1%. These results indicate that the application of Si promotes the development in plants under water deficit in function of promoting improvements in nutritional balance, providing a greater accumulation of Si in the cell wall and favoring the accumulation of biomass [28,12].…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…for the fresh and dry mass of the stem, reaching reductions of 59.8 and 97.1%. These results indicate that the application of Si promotes the development in plants under water deficit in function of promoting improvements in nutritional balance, providing a greater accumulation of Si in the cell wall and favoring the accumulation of biomass [28,12].…”
Section: Resultsmentioning
confidence: 77%
“…3D). The absorption and translocation did not occur efficiently due to the low root and xylem activity of the transporter, since the increase of the applied dose does not guarantee that it is absorbed by the plant [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curative effect of SiO2 in saline conditions was through breaking seed dormancy and internal phytohormonal regulation (Sun et al, 2021;Lee et al, 2010). SiO2 application in melon under saline conditions also alleviated the harmful effects of salinity by making an encouraging effect on vegetative growth parameters (Gomes et al, 2018). Silicon supplementation in calcium deficiency increased ascorbic acid, total phenol, carotenoid and photosystem II yield, and fresh and dry matter production in arugula plant.…”
Section: The Effects Of Exogenous Silicon Application On Germination ...mentioning
confidence: 98%
“…Fruits vegetables not accumulate Si as well as rice, but some studies have shown that this element may contribute to increase the photosynthetic rate and plant growth for some species such as eggplant and melon [15,16]. However, there is a lack of work about the interaction between Si and N in horticultural species such as eggplant, in terms of their influence on the accumulation of mineral and total nitrogen in the tissues of the plant.…”
Section: Introductionmentioning
confidence: 99%